Orientations for a popular Pastoral - Andina, Instituto de Pastoral (1973)
For two weeks (February 12-24, 1973) a "Popular Religiosity Course-Seminar" was held in Huampaní (Chaclacayo, Lima), organized by the former Pastoral Episcopal Commission. About 30 pastoral agents (priests and nuns) participated in it, who worked in the 8 pastoral zones of the country, although their participation in the seminar was in a personal capacity and they did not have any official representation of their respective work zone. The objectives of the course-seminar were, according to the official invitation document, a common reflection on popular religiosity, made by the same popular pastoral agents, to study "evangelization based on popular religiosity" and to draw up some concrete norms of popular ministry.